2000
DOI: 10.1021/ol006175v
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dipolar Cycloadditions as a Tool for the Preparation of Multivalent Structures

Abstract: The construction of multivalent structures such as sugar heterodimers, glycoclusters, calix sugars, multicalixarenes, and glycocyclodextrins is designed by using 1,3-dipolar cycloaddition as a versatile and efficient tool which allows the creation of heterocyclic bridges between the different units that are coupled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 42 publications
1
47
0
Order By: Relevance
“…Already in 2000 they reported a first example consisting in the reaction of heptakis(2,3-di-O-methyl-6-Opropargyl)bCD 36 and per-O-acetylated galactopyranosyl nitrile oxide 37 to give the corresponding isoxazole hepta-adduct 38 in 78% yield (Scheme 19). 105 In a later work, the same authors employed per-(C-6)-azido bCD as the dipolar partner for CuAAC click multiconjugation. The reactions with propargyl glycosides were conducted in organic solvents with either (Ph 3 P) 3 ÁCuBr or (Et 3 O) 3 PÁCuI as Cu(I) catalyst.…”
Section: 94mentioning
confidence: 99%
“…Already in 2000 they reported a first example consisting in the reaction of heptakis(2,3-di-O-methyl-6-Opropargyl)bCD 36 and per-O-acetylated galactopyranosyl nitrile oxide 37 to give the corresponding isoxazole hepta-adduct 38 in 78% yield (Scheme 19). 105 In a later work, the same authors employed per-(C-6)-azido bCD as the dipolar partner for CuAAC click multiconjugation. The reactions with propargyl glycosides were conducted in organic solvents with either (Ph 3 P) 3 ÁCuBr or (Et 3 O) 3 PÁCuI as Cu(I) catalyst.…”
Section: 94mentioning
confidence: 99%
“…Considering that the carbohydrate-protein interactions found in nature are multivalent to allow an efficient and specific recognition of such biomolecules, the immobilization of not only monovalent but also of multivalent carbohydrate displays over silica was planned by choosing the alkyne and azido monosaccharides 7 [33] and 8 [34] as well as the trivalent dendrons 12 and 13 which are readily obtainable by clickchemistry from the pentaerythritol derivative 9 [35] as depicted in Scheme 2. O-Alkylation with an excess of 2-chloroethyl ether [36] gave the trialkynyl derivative 10 suitable for click conjugation with 8.…”
Section: Resultsmentioning
confidence: 99%
“…To a solution of 9 [35] (0.250 g, 1 mmol) and Bu 4 NHSO 4 (0.678 g, 2 mmol) in 2-chloroethyl ether (5 mL) [36] was added aqueous NaOH (50 %, 5 mL). The two-phase reaction mixture was vigorously stirred at room temperature for 3 h. CH 2 Cl 2 (30 mL) and water (30 mL) were added , the organic phase separated and successively washed with water (2 50 mL).…”
Section: -{2-[2-(2-chloroethoxy)ethoxymethyl]-3-prop-2-ynyloxy-2-promentioning
confidence: 99%
“…[76][77][78][79] As a direct logical approach, many applications involve the conjugation of clickable sugar moieties onto appropriately functionalized macromolecular materials such as dendrimers and polymers. Following this approach, the construction of a series of precisely defined multivalent 1,4-disubsituted 1,2,3-triazole neoglycoconjugates, was reported by the group of SantoyoGonzalez using cycloaddition reactions either in the absence of a metal catalyst [80] or catalyzed by organic soluble copper complexes such as (Ph 3 P) 3 Á CuBr and (EtO) 3 P Á Cu(I) ( Figure 4A). [81] During the later study, it was found that microwave irradiation shortens the reactions' times considerably.…”
Section: Glycoconjugatesmentioning
confidence: 98%
“…On a different approach, Lee and coworkers [85] prepared glycoclusters using a carbohydrate structure, a galactose, as the core unit ( Figure 4C). By introducing four individual alkyne groups on methyl b-D-galactopyranoside they The Santoyo-González approach using organic-soluble copper complexes (Ph 3 P) Á CuBr and (EtO) 3 P Á Cu(I) and simultaneous microwave irradiation, [80,81] (B) Synthesis of multivalent, asymmetrical dendrimers as reported by the group of Hawker. [82] (C) Glycoclusters preparation using a carbohydrate structure as the core unit by Lee and coworkers.…”
Section: Glycoconjugatesmentioning
confidence: 99%